Peran Hati Nurani Hakim dalam Pemidanaan: Studi Normatif Hukum Pidana Indonesia dan Hukum Islam - Kholik, Muhamad Abdul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2026)
This study analyzes the role of judges' conscience in sentencing from the perspective of Indonesian criminal law and Islamic law. Through a qualitative normative approach, this study explores how judges' conscience functions as an ethically reflective mechanism in the modern justice system that is often trapped in procedural simulations. The focus of the study includes three main aspects: (1) the conceptual framework of judges' conscience in Indonesia's positive criminal law, (2) the meaning of conscience in the perspective of Islamic criminal law, and (3) the operational mechanism and accountability of judges' conscience in criminal practice. Research has found that the judge's conscience has the dual function of being a guardian of justice and ethical reflection, but requires translation into rational and tested legal language. The findings of the study show that the integration of the concept of conscience with positive legal frameworks and Islamic principles can strengthen the legitimacy of criminal judgments while ensuring the accountability of judges. The implications of this research are relevant for the development of criminal guidelines that accommodate the ethical dimension without sacrificing legal certainty